2007
DOI: 10.1261/rna.338407
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of yeast RNA-binding proteins Nrd1 and Nab3 with RNA polymerase II terminator elements

Abstract: Yeast RNA-binding proteins Nrd1 and Nab3 direct transcription termination of sn/snoRNA transcripts, some mRNA transcripts, and a class of intergenic and anti-sense transcripts. Recognition of Nrd1-and Nab3-binding sites is a critical first step in the termination and subsequent processing or degradation of these transcripts. In this article, we describe the purification and characterization of an Nrd1-Nab3 heterodimer. This Nrd1-Nab3 complex binds specifically to RNA sequences derived from a snoRNA terminator.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
172
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(185 citation statements)
references
References 34 publications
11
172
0
2
Order By: Relevance
“…For each of these genes, we observed a peak of Nab3 binding at the 5= end of the transcript. Nab3 forms a heterodimer with Nrd1 (8,16), and many ncRNA terminators require both factors for efficient termination (9,32,41). One of the genes upregulated in response to Nrd1 depletion is the ammonium permease gene MEP2.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each of these genes, we observed a peak of Nab3 binding at the 5= end of the transcript. Nab3 forms a heterodimer with Nrd1 (8,16), and many ncRNA terminators require both factors for efficient termination (9,32,41). One of the genes upregulated in response to Nrd1 depletion is the ammonium permease gene MEP2.…”
Section: Resultsmentioning
confidence: 99%
“…The precise binding sites for Nrd1 and Nab3 can be determined from the presence of T-to-C transitions caused by the 4-thiouracil cross-link (49,50). Using these T-to-C transitions to find the binding sites, we analyzed the top 40 Nab3 binding peaks among NCR genes and found common motifs corresponding to known Nrd1 and Nab3 binding sites (Table S1) (15)(16)(17)(18)(19). Using MEME software (51), we found that the Nrd1 consensus is present in fewer genes but is more statistically significant while the Nab3 consensus is present more often but contains less information (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, NRD1 and SEN1 mutations cause strong termination defects at some snoRNAs (Kim et al 2006). Nrd1 and Nab3 recognize specific RNA sequences located downstream from the mature 39-end of sn/snoRNAs (GUAA/G and UCUU, respectively) Brow 1996, 1998;Conrad et al 2000;Steinmetz et al 2001;Carroll et al 2004Carroll et al , 2007, and mutations in these sites cause termination defects (Carroll et al 2004). Several snoRNA terminators contain multiple potential binding sites for Ndr1 and Nab3, which form a heterodimer (Carroll et al 2007).…”
Section: The Nrd1 Complexmentioning
confidence: 99%